Adsorption, structural alteration and elution of peptides at pendant PEO layers - Wu, Xiangming (2013)
An experimentally based, quantitative understanding of the entrapment and function of small peptides within PEO brush layers does not currently exist. Earlier work provided a rationale for expecting that an ordered, compact peptide will enter the PEO phase more readily than a peptide of similar size that adopts a less ordered, less compact form, and that amphiphilicity will promote peptide retention within the hydrophobic region of the PEO brush. Here we more deliberately describe criteria for peptide integration and structural change within the PEO brush, and discuss the reversibility of peptide entrapment with changing solvent conditions. For this purpose, circular dichroism (CD) was used to record the adsorption and conformational changes of (amphiphilic) WLBU2 and (non-amphiphilic) polyarginine peptides at uncoated (hydrophobic) and PEO-coated silica nanoparticles. Peptide conformation was controlled between disordered and α-helical forms by varying the concentration of perchlorate ion. We show an initially more ordered (α-helical) structure promotes peptide adsorption into the PEO layer. Further, a partially helical peptide undergoes an increase in helicity after entry, likely due to concomitant loss of capacity for peptide-solvent hydrogen bonding. Peptide interaction with the PEO chains resulted in entrapment and conformational change that was irreversible to elution with changing solution conditions in the case of the amphiphilic peptide. In contrast, the adsorption and conformational change of the non-amphiphilic peptide was reversible. These results indicate that responsive drug delivery systems based on peptide-loaded PEO layers can be controlled by modulation of solution conditions and peptide amphiphilicity.